The Association Between Bangladeshi Adults’ Demographics, Personal Beliefs, and Nutrition Literacy: Evidence From a Cross-Sectional Survey - Banna, Md. Hasan Al; Hamiduzzaman, Mohammad; Kundu, Satyajit; Ara, Tasnu; Abid, Mohammad Tazrian; Brazendale, Keith; Seidu, Abdul-Aziz; Disu, Tasnim Rahman; Mozumder, N. H. M. Rubel; Frimpong, James Boadu; Khan, Md Shafiqul Islam (Frontiers in Nutrition, 2022)
Background: Poverty and health illiteracy, combined with inappropriate systems to track disease and infection rates, contribute to children-and-mothers’ poor adherence to nutrient-rich foods intake in Bangladesh. Although risk factors for child and pregnant women malnutrition have been explored, the relationship between Bangladeshi adults’ nutrition literacy and their demographics and personal beliefs remains unknown. The purpose of this study was to examine the association between adults’ nutrition literacy, demographics and personal beliefs in a large sample of Bangladeshi adults. Methods: Four hundred adults from two districts (Dhaka and Chattogram) of Bangladesh participated in a cross-sectional survey. Data were collected by interviews using a structured questionnaire containing the Nutrition Literacy Scale. Multiple linear regression models were employed to analyze associations between nutrition literacy and related factors. Results: The mean nutrition literacy score was 21.6 (SD: 3.7; range: 11-32) on a scale of 32. Multiple linear regression revealed that being a businessman (β=1.66, p=0.013) or private employee (β=1.08, p=0.030), having a higher family income (β=1.17, p=0.009), and a higher educational level were positively associated with higher nutrition literacy scores compared to their counterparts. Participants who had ever completed a nutrition-related course (β=4.95, p<0.001), and who perceived themselves as having a need for accessing nutrition-related information were positively associated with the higher nutrition literacy compared to their counterparts. Conclusions: Findings from this study suggest the need for an integrated response plan involving educational interventions and accessible dietary plans targeting adult populations to enhance their nutritional literacy.